Chemotherapy effect on myocardial fibrosis markers in patients with gynecologic cancer and low cardiovascular risk - Ye, Lu; Wang, Dan-qing; Yang, Meng-xi; Li, Qing-li; Luo, Hong; Lin, Xiao-juan; Li, Ke-min; Song, Liang; Ma, Yu; Huang, Hui-qiong; Zhong, Lan; Yang, Lu; et al. (Frontiers in Oncology, 2023)
Background: Patients with gynecologic cancers experience side effects of chemotherapy cardiotoxicity. We aimed to quantify cardiac magnetic resonance (CMR) markers of myocardial fibrosis in patients with gynecologic cancer and low cardiovascular risk who undergo chemotherapy.Methods: This study is part of a registered clinical research. CMR T1 mapping was performed in patients with gynecologic cancer and low cardiovascular risk undergoing chemotherapy. The results were compared with those of age-matched healthy control subjects.Results: 68 patients (median age = 50 years) and 30 control subjects were included. The median number of chemotherapy cycles of patients was 9.0 (interquartile range [IQR] 3.3-17.0). Extracellular volume fraction (ECV) (27.2% ± 2.7% vs. 24.5% ± 1.7%, P < 0.001) and global longitudinal strain (−16.2% ± 2.8% vs. −17.4% ± 2.0%, P = 0.040) were higher in patients compared with controls. Patients with higher chemotherapy cycles ( ﹥ 6 cycles) (n=41) had significantly lower intracellular mass indexed (ICMi) compared with both patients with lower chemotherapy cycles (≤6 cycles) (n=27) (median 27.44 g/m 2 [IQR 24.03-31.15 g/m 2 ] vs. 34.30 g/m 2 [IQR 29.93-39.79 g/m 2 ]; P = 0.002) and the control group (median 27.44 g/m 2 [IQR 24.03-31.15 g/m 2 ] vs. 32.79 g/m 2 g/m 2 ]; P = 0.002). Patients with two or more chemotherapy regimens had significantly lower ICMi compared with both patients with one chemotherapy regimen (27.45 ± 5.16 g/m 2 vs. 33.32 ± 6.42 g/m 2 ; P < 0.001) and the control group (27.45 ± 5.16 g/m 2 vs. 33.02 ± 5.52 g/m 2 ; P = 0.002). The number of chemotherapy cycles was associated with an increase in the ECV (Standard regression coefficient [β] = 0.383, P = 0.014) and a decrease in the ICMi (β = -0.349, P = 0.009).Patients with gynecologic cancer and low cardiovascular risk who undergo chemotherapy have diffuse extracellular volume expansion, which is obvious with the increase of chemotherapy cycles. Myocyte loss may be part of the mechanism in patients with a higher chemotherapy load.